Do Technology Changes Affect The Productivity of The Indonesian Islamic Rural Bank (BPRS)? - Aam; Aisyah As-Salafiyah (Tamkin Journal, 2022)
The Islamic financial industry in Indonesia is currently a global concern, one of which is bank financial institutions, so measuring productivity is essential for Islamic rural banks (BPRS) in Indonesia. This study tries to analyze the BCC model as a basic model to see the level of productivity in a BPRS using the Malmquist productivity index, both in terms of changes in efficiency and changes in technology. The results obtained from the Malmquist index score or total productivity change (TFPCH) show that, in general, BPRS has experienced a decline in productivity but has increased in the last two years. However, there are six BPRS out of 16 BPRS that get an average score of more than one and show an increase in productivity. The BPRS with the highest productivity level score is PT BPD East Kalimantan and North Kalimantan, and the BPRS with the lowest productivity level score is PT BPD Central Java (UUS). However, East Java still has not reached the optimal level of productivity, with a score of 0.803. Overall, the priority factor that needs to be improved in BPRS is the rate of change in technological innovation. This research shows that BPRS needs to implement digitalization.